The handbook of global communication and media ethics - Fortner, Robert S.; Fackler, Mark (Handbooks in communication and media, 2011)
"This groundbreaking collection provides a comprehensive picture of the ethical dimensions of communication in a global setting. Bringing together scholars from around the world, this substantial work examines ethical issues raised by globalization, the practice of journalism, popular culture, and media activities, and provides the most detailed and diverse set of essays ever assembled on this vital topic. The editors, along with a team of international communication and media scholars, provides an authoritative overview of the philosophical and theoretical issues associated with global communication and media ethics, including examinations of feminism, ideology, social responsibility, reporting, metanarratives, blasphemy, development, and glocalism, among many others. In addition, the handbook includes international case studies addressing topics such as reporting, censorship, responsibility, terrorism, disenfranchisement, and guilt. The work includes contributions by several Islamic scholars discussing various facets of that religion's engagement with the public sphere, as well as essays dealing with the religious and cultural factors that complicate efforts to understand our world. Fortner and Fackler's innovative collection is both theoretical and practical, and will raise the ethical bar for both scholars and practitioners in the world of global communication and media"--Provided by publisher.